Development Of A Hot-Fit Framework For Hmis: Empirical Study And Technical Implications At A Regional General Hospital - Frendy Rumambi (Jurnal Sistem Informasi Bisnis, 2025)
The digitalization of the health industry has allowed hospitals to adopt a Hospital Information System (HIS) for enhancing the efficiency, transparency and quality of services. Even though the application of HIS is regulated nationally, the success in its adoption in Indonesia is considered varied, Dr. Samaratulagi Tondano Regional Hospital in Minahasa Regency, North Sulawesi is no exception. This research is focused on the development and application of the novel model, Extended HOT-Fit Framework, by incorporating Data Quality as the new dimension under Technology domain. The study adopted quantitative approach and applied Structural Equation Modeling (SEM) to evaluate the variables’ interrelationships. A survey of 150 respondents, all active users of SIRS, was conducted. The research instrument was designed according to the adapted 2006 HOT-Fit model. The results analysis indicates that Data Quality enhances the ability of the model to explain user satisfaction, the net benefit of the system. Moreover, System Quality and Service Quality dimensions also significantly impact user satisfaction, and organizational factors (Structure and Environment) have indirect impact on net benefits. This study provides empirical and technical contribution to the development of model for SIRS success evaluation in Indonesia. From a practical point of view, findings of this study can assist hospital managers in devising better improvement strategies for data quality and system integration in SIRS implementation.